Dietary exposure and risk assessment of exposure to hexabromocyclododecanes in a Taiwan population. (June 2019) - Lee, Ching-Chang; Chang, Wei-Hsiang; Chen, Hsiu-Ling
Abstract: Hexabromocyclododecane (HBCD) is commonly used in commercial products and factories. HBCDs can be detected in the air, bioaccumulated deposits, water, soil, sediments, and in biota and foodstuffs in the food-chain because they are not chemically bound to the polymer. We determined the levels of α-, β-, and γ-HBCDs in 270 foodstuffs and the doses of HBCDs Taiwanese are normally exposed to. We also wanted to create a strategy of risk management for HBCDs based on margins of exposure ( MOE ). HBCDs were frequently detectible in fish, seafood, and poultry. Their highest concentrations were in fish, oil, poultry, and livestock. The highest estimated daily intake was in 0- to 3-year-olds (1.576 ng/kg/day), and lower in 3- to 6- (1.064 ng/kg/day), 6- to 12- (0.899 ng/kg/day), and lowest in 12- to 16- (0.632 ng/kg/day) year-olds. The exposure doses to HBCDs indicated no health concern for Taiwanese. Except for fish, significant concentrations of α- and γ-HBCDs were detected in many other foodstuffs, which might indicate that exposure to HBCD is a relatively recent problem. Therefore, one goal of a management policy should be to follow-up the flow direction of HBCDs in Taiwan. Graphical abstract: Image 1 Highlights: α-, β-, and γ-HBCD were detected in 270 foodstuffs. The highest level of HBCDs were in fish, oil, poultry, and livestock. Current dietary exposure to HBCDs was not a serious health concern. The accumulation of HBCD recently happened.